Physical Education, Sports and Health in Shaping Character Values - Nurfauziah, Erika; Farhanah, Shafa Zilanisa; Azahra, Azahra; Setiawan, Muhammad Arief; Rahayu, Selvia (Jurnal MensSana, 2025)
Physical Education, Sports, and Health (PJOK) is an essential part of the education system, focusing not only on students' physical growth but also on shaping their character values. Students gain hands-on experience that fosters positive attitudes such as discipline, responsibility, cooperation, honesty, and sportsmanship through various games, sports, and physical activities. PJOK learning enables students to interact socially, appreciate differences, and learn to persevere when faced with difficulties. Furthermore, PJOK enhances emotional skills such as self-control and respect for rules. This includes enhancing cognitive, affective, and psychomotor self-confidence. PJOK also helps build emotional skills such as self-control, respect for rules, and self-confidence. Therefore, PJOK not only helps improve motor skills and physical fitness but also helps build a balanced character across cognitive, affective, and psychomotor domains. This aligns with the national education goal of creating a healthy, competitive generation with noble qualities that benefit society, the nation, and the state.